Fundamentals of corporate finance - Brealey, Richard A. (McGraw-Hill series in finance, 1995)
This text balances core coverage of the fundamental topics in corporate finance with an emphasis on modern business decision-making. The key principles and mechanics of the time value of money - a central concept - are carefully detailed and illustrated.